(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, presents the results of the research of the mineral content of "Bayan Shirey" white wine and "Hingdoh" red wine made from grape varieties grown in Fergana region by inductively coupled plasma optical emission spectrometry method. According to the results of the analysis, 23 elements out of 30 studied elements were determined in "Bayan Shirey" and "Hingdohni" wines. It was found that the amount of macro and micronutrients in "Hingdohni" red wine is 1,626 times higher than that of "Bayan Shirey" white wine. The amount of macroelements such as potassium, magnesium, phosphorus, calcium, sodium and sulfur was determined, and macroelements made up 97.87% of the total amount of minerals in "Bayan Shirey" and 98.29% in "Hingdohni". Potassium has the highest amount, its amount is 75.56% of the mineral composition of "Bayan Shirey" and 78.18% of "Hingdohni". It was shown that the amount of elements such as silicon, boron, iron, strontium, aluminum, manganese, zinc, selenium, lithium and copper is more than the rest of microelements. No toxic elements were detected in the studied wines.